2019
DOI: 10.1002/sono.12208
|View full text |Cite
|
Sign up to set email alerts
|

Determining if simulation is effective for training in ultrasound: A narrative review

Abstract: Simulation allows students to learn fundamental skills, such as trial and error, critical thinking, and cognitive and motor skills in a safe environment that closely represents reality. Presently, there are large amounts of literature surrounding simulation in the health and medical field. The aim of this paper is to review the current literature surrounding simulation in medical ultrasound to assess if simulation is effective in teaching sonography skills, and if simulation can be used as a substitute for edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…In this study, first-trimester ultrasound and clinical pathology that were unavailable for demonstration on live models were instead demonstrated using high-fidelity simulators, which provided a safe, patient-free learning environment, and were highly rated/commended by the training participants. Ideally, training should utilise both simulated and real-life patients with strictly limited scanning times for pregnant volunteers and heavier reliance on phantom models and virtual/simulation technologies in early training [ 70 – 72 ] as recommended by the ISUOG [ 41 ]. This reduces reliance on pregnant volunteers and provides the opportunity to scan simulated first-trimester pregnancies, often lacking in training courses due to the early gestation of the fetus and associated risk of identifying an unexpected abnormality in volunteers who are yet to receive formal scanning.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, first-trimester ultrasound and clinical pathology that were unavailable for demonstration on live models were instead demonstrated using high-fidelity simulators, which provided a safe, patient-free learning environment, and were highly rated/commended by the training participants. Ideally, training should utilise both simulated and real-life patients with strictly limited scanning times for pregnant volunteers and heavier reliance on phantom models and virtual/simulation technologies in early training [ 70 – 72 ] as recommended by the ISUOG [ 41 ]. This reduces reliance on pregnant volunteers and provides the opportunity to scan simulated first-trimester pregnancies, often lacking in training courses due to the early gestation of the fetus and associated risk of identifying an unexpected abnormality in volunteers who are yet to receive formal scanning.…”
Section: Discussionmentioning
confidence: 99%
“…A review on the effectiveness of simulation for beginners in ultrasound training determined that when students moved from simulation to model patients, their level of competence did not reach a level that would allow them to scan patients unsupervised. [ 129 ] Through multiple studies comparing the outcomes of computer simulation versus live models, a common theme was that students still needed access to live models to hone their communication and scanning skills. This was particularly the situation with obstetric scanning, where simulators with static “fetus” do not reflect the clinical situation of mobile babies.…”
Section: Simulators In Student and Trainee Ultrasound Educationmentioning
confidence: 99%
“…In a literature review spanning over 19 studies, US simulation with task trainers not only showed an improvement in student confidence but had superior learning outcomes when compared with theoretical teaching strategies alone. 2 The necessity of realistic simulation in conjunction with clinical experience throughout medical education is evident. This is especially true in case of hospital-based learning, as practitioner training is often a by-product of the facility's main objective: patient care and outcomes.…”
Section: Introductionmentioning
confidence: 99%